Validating the rhenium proxy for rock organic carbon oxidation using weathering profiles - Katherine E. Grant; Mathieu Dellinger; Alexander J. Dickson; Mateja Ogric; Kate Horan; Steven Petsch; Robert G. Hilton (Chemical Geology, 2025)

Millennial‐aged organic carbon subsidies to a modern river food web - Nina Caraco; James E. Bauer; Jonathan J. Cole; Steven Petsch; Peter Raymond (Ecology, 2010)
Recent studies indicate that highly aged material is a major component of organic matter transported by most rivers. However, few studies have used natural 14 C to trace the potential entry of this aged material into modern river food webs. Here we use natural abundance 14 C, 13 C, and deuterium ( 2 H) to trace the contribution of aged and contemporary organic matter to an important group of consumers, crustacean zooplankton, in a large temperate river (the Hudson River, New York, USA). Zooplankton were highly 14 C depleted (mean Δ 14 C = −240‰) compared to modern primary production in the river or its watershed (Δ 14 C = −60‰ to +50‰). In order to account for the observed 14 C depletion, zooplankton must be subsidized by highly aged particulate organic carbon. IsoSource modeling suggests that the range of the aged dietary subsidy is between ~57%, if the aged organic matter source was produced 3400 years ago, and ~21%, if the organic carbon used is ≥50 000 years in age, including fossil material that is millions of years in age. The magnitude of this aged carbon subsidy to river zooplankton suggests that modern river food webs may in some cases be buffered from the limitations set by present‐day primary production.